PERAN RASA MALU DAN RASA BERSALAH TERHADAP PENGAJARAN MORAL ANAK - Nurhayani Hayani (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2017)
Each human’s emotion develop in certain meaning. It means that loosing negative emotions in our understanding about child development is same as loosing one of basic colour in painter’s self; and not only the basic colour will loose but a million colours which are created from combination of colours and basic colour. Negative emotion such as shame and guil will be more useful than positive emotion when someone learn to change his behavior.Negative emotion will motivate children to learn and practice prosocial behavior. It will effect directly to children’s behavior and personality because extreme emotion gives deep effect to motivate them in doing kindness which is hoped others. Shame and guilt are not emotion which must be disappeared. Shame and guilt will teach moral values to children if we use correctly.Key words: moral emotion, shame, guilt, children’s moral, moral development.